Preparation method of positive electrode for solid-state battery

By preparing lithium-rich manganese-based ternary cathode material and adding binary composite conductors with modified carbon nanotubes and carbon black, the problem that traditional cathode materials cannot meet higher requirements is solved, the electrochemical performance and cycle stability are significantly improved, and the long cycle performance and rate performance of the battery are enhanced.

CN119581497AActive Publication Date: 2025-03-07GUIZHOU HANGSHENG LITHIUM ENERGY TECH CO LTD +1
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411809387.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-10
Publication Date
2025-03-07
Estimated Expiration
2044-12-10

AI Technical Summary

Technical Problem

In existing lithium-ion batteries, traditional positive electrode materials cannot meet higher electrical performance requirements and pose safety risks.

Method used

A method for preparing a positive electrode for solid-state batteries is adopted. By mixing the positive electrode material, binder and conductive agent, drying and rolling, a lithium-manganese-based ternary positive electrode material is prepared, and a binary composite conductive agent with modified carbon nanotubes and carbon black is added to improve electrochemical performance and cycle stability.

Benefits of technology

It significantly improves the electrochemical performance and cycle stability of the positive electrode, enhances the long cycle performance and rate performance of the battery, solves the problem that traditional positive electrode materials cannot meet higher requirements, and improves the safety of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses a preparation method of a positive electrode for a solid-state battery, and belongs to the technical field of lithium ion batteries. Comprising the following raw materials in parts by weight: 80-100 parts of a positive electrode material, 6-12 parts of a binder and 10-20 parts of a conductive agent. According to the prepared positive electrode, the positive electrode material is a lithium-rich manganese-based ternary positive electrode material and is large in capacity and low in cost, and the positive electrode material is treated by phosphate, so that the electrochemical performance and the cycling stability of the positive electrode are improved; wherein the conductive agent is a binary composite conductive agent of carbon nanotubes and carbon black and can significantly enhance the cycling stability and electrical performance of the electrode, and moreover, through modification of the carbon nanotubes, compared with common carbon nanotubes, the carbon nanotubes have more defect types and active sites, few impurities are generated, and the performance of the electrode is improved. And the long cycle performance and the rate capability of the electrode can be further enhanced. In conclusion, the prepared positive electrode has important application value in the technical field of lithium ion batteries.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of lithium-ion batteries, and in particular, relates to a method for preparing a positive electrode for a solid-state battery. Background Art

[0002] Nowadays, oil resources are becoming increasingly scarce and environmental pollution is becoming increasingly serious. The harmonious development of energy, resources, environment and human society has become the focus of attention. In order to solve the increasingly serious environmental problems and reduce dependence on and emissions from fossil fuels, it is urgent to develop new energy that is efficient, green and environmentally friendly. As people pay more attention to low-carbon travel, the market demand for low-emission or zero-emission electric vehicles is increasing, which has also promoted the development of lithium-ion batteries.

[0003] Lithium-ion batteries have the advantages of high energy density, long cycle life, and no memory effect. As commercialized high-efficiency energy storage devices, they are widely used in daily life and production. However, the safety hazards caused by flammable organic electrolytes in commercial lithium-ion batteries are still a major challenge that plagues lithium-ion batteries, especially in large-scale applications such as electric vehicles and energy storage power stations. There is no liquid in solid-state batteries, and the gaps inside and on the interfaces of electrodes and diaphragms are not filled with liquid. The conduction path of ions relies entirely on solid contact, which can fundamentally solve the safety problems of lithium-ion batteries.

[0004] At present, most of the research on all-solid-state lithium-ion batteries focuses on solid electrolytes, while there is less research on positive electrodes. The composite positive electrode of lithium-ion batteries is composed of positive electrode active materials, inorganic solid electrolytes and conductive additives. The inorganic solid electrolyte is introduced to provide a transmission channel for lithium ions; the conductive additive is introduced to provide an electron transmission channel; the contact area between the electrolyte and the positive electrode active material is increased to effectively solve the interface problem, shorten the migration distance of lithium ions in the positive electrode active material with low lithium ion conductivity, and ensure the full redox reaction of the positive electrode active material during the battery charging and discharging process. However, with the continuous improvement of people's requirements, traditional positive electrode materials can no longer meet the requirements. Therefore, it is urgent to invent a positive electrode for solid-state batteries with excellent electrical properties to meet the higher requirements in the field of lithium-ion battery technology. Summary of the invention

[0005] The purpose of the present invention is to overcome the defects of the prior art and provide a method for preparing a positive electrode for a solid-state battery.

[0006] The purpose of the present invention can be achieved through the following technical solutions: A method for preparing a positive electrode for a solid-state battery comprises the following steps: A1. After the positive electrode material, binder and conductive agent are placed in an oven and dried for 12 hours, the binder is first dissolved in N-methylpyrrolidone (NMP), and then the conductive agent and positive electrode material are added and mixed, and then placed in a homogenizer and stirred to obtain a positive electrode slurry; A2. Place aluminum foil on the surface of the coating machine, pour in the positive electrode slurry prepared in step A1, adjust the scale of the knife to 12μm, remove it when it is coated at a uniform speed to the end, and then place it in an oven at 120°C to dry for 1h, then roll it, and then punch it manually to obtain the positive electrode for solid-state batteries.

[0007] Furthermore, the raw materials are calculated in parts by weight as follows: 80-100 parts of positive electrode material, 6-12 parts of binder, and 10-20 parts of conductive agent.

[0008] Furthermore, in step A1, the stirring conditions are firstly homogenizing at 800 rpm for 30 seconds and then homogenizing at 2000 rpm for 15 minutes.

[0009] Furthermore, in step A1, the binder is one of polyvinylidene fluoride and polytetrafluoroethylene.

[0010] Furthermore, the positive electrode material is prepared by the following steps: The lithium-rich manganese-based ternary material and PVP-K30 were dissolved and dispersed in a mixed solution of anhydrous ethanol and distilled water, and then ammonium dihydrogen sulfate was added. After ultrasonic treatment for 15 minutes, the components were evenly dispersed. Then, after continuous stirring for 3 hours, they were dried in a vacuum drying oven at 100°C for 6 hours, and finally calcined at 450°C for 5 hours and naturally cooled to room temperature to obtain the positive electrode material.

[0011] Furthermore, the ratio of the amount of the lithium-rich manganese-based ternary material, PVP-K30 and ammonium dihydrogen sulfate is 10g:6.5g:8.4g.

[0012] The prepared positive electrode material is a lithium-rich manganese-based ternary positive electrode material with large capacity and low cost. By treating the positive electrode material with phosphate as a surface inducer, a NiO rock salt phase protective layer can be formed on the surface of the positive electrode material. The protective layer has a stable structure, which improves the stability of the layered structure of the material and inhibits the continuous transformation of the layered structure to the spinel structure, thereby significantly improving the electrochemical performance. Not only that, the modified structure can also prevent oxygen from escaping, while physically blocking the side reactions of high-valent metal ions and electrolytes, thereby inhibiting surface reconstruction and improving the cycle stability of the electrode.

[0013] Furthermore, the conductive agent is prepared by the following steps: S1. Mix multi-walled carbon nanotubes with concentrated sulfuric acid and concentrated nitric acid, and perform ultrasonic treatment. The ultrasonic time is 4 hours and the ultrasonic temperature is 60°C. After the ultrasonic treatment, reflux at 100°C for 5 hours. After the reaction is completed, cool, vacuum filter with a polytetrafluoroethylene filter membrane, wash the filtrate with distilled water until it is neutral, dry it in a vacuum drying oven at 100°C, and grind it to obtain pre-modified carbon nanotubes. The ratio of multi-walled carbon nanotubes, concentrated sulfuric acid, and concentrated nitric acid is 1g:60mL:40mL. S2. In a three-necked flask equipped with a stirring device, vinyl triethoxysilane, AIBN (azobisisobutyronitrile) and N,N-dimethylformamide (DMF) were mixed and stirred evenly, 2-mercaptopyridine was slowly added, and the temperature of the system was maintained at 70°C. The reaction was carried out for 4 hours. After the reaction was completed, part of the solvent was first removed by rotary evaporation, and then purified by column chromatography (the eluent was a mixed solvent of benzene / ethyl acetate, and the volume ratio of the two was 1:3). The eluent was removed by rotary evaporation to obtain an intermediate; the ratio of the amount of vinyl triethoxysilane, AIBN, N,N-dimethylformamide and 2-mercaptopyridine was 18.8g:0.3g:100mL:11.1g; Under the action of AIBN, the unsaturated carbon-carbon double bond on the vinyltriethoxysilane molecule undergoes a thiol-ene click reaction with the thiol group of 2-thiopyridine to obtain an intermediate. S3, mixing the pre-modified carbon nanotubes with the ethanol aqueous solution, adding them to a magnetic stirring device, adding a magnet, starting stirring, dispersing for 30 minutes, so that the pre-modified carbon nanotubes are evenly dispersed in the ethanol aqueous solution, evacuating the device, passing N2 gas, then adding the intermediate, starting heating, setting 80°C, turning on condensation water, reacting for 4 hours, the reaction is completed, filtering, washing with ethanol, and then drying in a vacuum drying oven for 3 hours to obtain modified carbon nanotubes; the ratio of the amount of pre-modified carbon nanotubes, ethanol aqueous solution, and intermediate is 1.0g:100mL:8.5g; S4, adding the modified carbon nanotubes and carbon black into a ball mill, and mixing them evenly by ball milling to obtain a conductive agent; the ratio of the modified carbon nanotubes to the carbon black is 5g:2g; The prepared conductive agent is a binary composite conductive agent. Compared with a single conductive agent, it can construct a multi-dimensional conductive network in the electrode system, increase the probability of contact between active material particles and the conductive agent, increase the active sites of chemical reactions, shorten the transmission distance of ions and electrons in the electrode system, weaken the polarization of the battery, and enhance the cycle stability of the electrode. In addition, carbon nanotubes have excellent electrical and thermal conductivity, which promotes the transfer of heat in the electrode material and avoids the reduction of the battery safety factor due to high temperature at the point. At the same time, the overlap and entanglement between carbon nanotubes and active materials enhances the toughness of the electrode, and the active material is not easy to peel off during the charging process. Furthermore, the service life of the positive electrode is improved; more than that, the impurities in the carbon nanotubes are removed and the purity is improved through modification of the carbon nanotubes; the introduced silicon element can form wrinkles on the surface of the carbon nanotubes, further increasing the specific surface area of ​​the carbon nanotubes and thus enhancing their electrical properties; the introduction of the sulfur element can effectively improve the capacity and rate performance of the carbon nanotubes; the introduction of the nitrogen element significantly increases the number of defect points and vacancies in the plane of the carbon nanotubes, which can significantly improve the long cycle performance of the battery; finally, compared with single-atom doping, this multi-doping can provide carbon nanotubes with more defect types and active sites, further improving the electrical properties of the material.

[0014] Beneficial effects of the present invention: The positive electrode prepared by the present invention has a lithium-rich manganese-based ternary positive electrode material, which has a large capacity and low cost. The positive electrode material is treated with phosphate to improve the electrochemical performance and cycle stability of the positive electrode; the cycle stability and electrical performance of the electrode can be significantly enhanced by adding a binary composite conductive agent of carbon nanotubes and carbon black. Moreover, by modifying the carbon nanotubes, compared with ordinary carbon nanotubes, there are more defect types and active sites, and less impurities, which can further enhance the long cycle performance and rate performance of the electrode. In summary, the positive electrode prepared by the present invention has important application value in the field of lithium-ion battery technology. DETAILED DESCRIPTION

[0015] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0016] Embodiment 1

[0017] Preparation of conductive agent: S1. Mix 1 g of multi-walled carbon nanotubes with 60 mL of concentrated sulfuric acid and 40 mL of concentrated nitric acid, and perform ultrasonic treatment. The ultrasonic time is 4 h and the ultrasonic temperature is 60°C. After the ultrasonic treatment, reflux at 100°C for 5 h. After the reaction is completed, cool, vacuum filter with a polytetrafluoroethylene filter membrane, wash the filtrate with distilled water until it is neutral, dry it in a vacuum drying oven at 100°C, and grind it to obtain pre-modified carbon nanotubes; S2. In a three-necked flask equipped with a stirring device, 18.8 g of vinyl triethoxysilane, 0.3 g of AIBN and 100 mL of N, N-dimethylformamide were mixed and stirred evenly, and 11.1 g of 2-mercaptopyridine was slowly added, and the temperature of the system was maintained at 70 ° C. The reaction was carried out for 4 hours. After the reaction was completed, part of the solvent was first removed by rotary evaporation, and then purified by column chromatography (the eluent was a mixed solvent of benzene / ethyl acetate, and the volume ratio of the two was 1:3), and the eluent was removed by rotary evaporation to obtain an intermediate; S3, 1.0g of pre-modified carbon nanotubes were mixed with 100mL of ethanol aqueous solution, added to a magnetic stirring device, a magnet was added, stirring was started, and the pre-modified carbon nanotubes were dispersed for 30min to make the pre-modified carbon nanotubes uniformly dispersed in the ethanol aqueous solution, the device was evacuated, N2 gas was introduced, and 8.5g of the intermediate was added, and heating was started, set to 80°C, condensed water was turned on, and the reaction was carried out for 4h. After the reaction was completed, the modified carbon nanotubes were filtered, washed with ethanol, and then dried in a vacuum drying oven for 3h to obtain modified carbon nanotubes; S4. Add 5 g of modified carbon nanotubes and 2 g of carbon black into a ball mill, and mix them evenly by ball milling to obtain a conductive agent.

[0018] Embodiment 2 Preparation of conductive agent: S1. Mix 2 g of multi-walled carbon nanotubes with 120 mL of concentrated sulfuric acid and 80 mL of concentrated nitric acid, and perform ultrasonic treatment. The ultrasonic time is 4 h and the ultrasonic temperature is 60 ° C. After the ultrasonic treatment, reflux at 100 ° C for 5 h. After the reaction is completed, cool, vacuum filter with a polytetrafluoroethylene filter membrane, wash the filtrate with distilled water until it is neutral, dry it in a vacuum drying oven at 100 ° C, and grind it to obtain pre-modified carbon nanotubes; S2. In a three-necked flask equipped with a stirring device, 37.6 g of vinyl triethoxysilane, 0.6 g of AIBN and 200 mL of N, N-dimethylformamide were mixed and stirred evenly, and 22.2 g of 2-mercaptopyridine was slowly added, and the temperature of the system was maintained at 70°C. The reaction was carried out for 4 hours. After the reaction was completed, part of the solvent was first removed by rotary evaporation, and then purified by column chromatography (the eluent was a mixed solvent of benzene / ethyl acetate, and the volume ratio of the two was 1:3), and the eluent was removed by rotary evaporation to obtain an intermediate; S3, 2.0g of pre-modified carbon nanotubes were mixed with 200mL of ethanol aqueous solution, added to a magnetic stirring device, a magnet was added, stirring was started, and the pre-modified carbon nanotubes were dispersed for 30min to make the pre-modified carbon nanotubes uniformly dispersed in the ethanol aqueous solution, the device was evacuated, N2 gas was introduced, and 17g of the intermediate was added, and heating was started, set to 80°C, condensed water was turned on, and the reaction was carried out for 4h. After the reaction was completed, the modified carbon nanotubes were filtered, washed with ethanol, and then dried in a vacuum drying oven for 3h to obtain modified carbon nanotubes; S4. Add 10 g of modified carbon nanotubes and 4 g of carbon black into a ball mill, and mix them evenly by ball milling to obtain a conductive agent.

[0019] Embodiment 3

[0020] Preparation of positive electrode materials: 10g of lithium-rich manganese-based ternary material and 6.5g of PVP-K30 were dissolved and dispersed in a mixed solution of anhydrous ethanol and distilled water, and then 8.4 g of ammonium dihydrogen sulfate was added and ultrasonicated for 15 minutes to make the components evenly dispersed. Then, the mixture was stirred continuously for 3 hours and dried in a vacuum drying oven at 100°C for 6 hours. Finally, the mixture was calcined at 450°C for 5 hours and naturally cooled to room temperature to obtain the positive electrode material.

[0021] Embodiment 4

[0022] Preparation of positive electrode materials: 20g of lithium-rich manganese-based ternary material and 13.0g of PVP-K30 were dissolved and dispersed in a mixed solution of anhydrous ethanol and distilled water, and then 16.8g of ammonium dihydrogen sulfate was added. After ultrasonic treatment for 15 minutes, the components were evenly dispersed. Then, after continuous stirring for 3 hours, the mixture was dried in a vacuum drying oven at 100°C for 6 hours, and finally calcined at 450°C for 5 hours and naturally cooled to room temperature to obtain the positive electrode material.

[0023] Embodiment 5

[0024] A1. After drying 80 g of the positive electrode material prepared in Example 3, 6 g of polyvinylidene fluoride and 10 g of the conductive agent prepared in Example 1 in an oven for 12 h, the polyvinylidene fluoride was first dissolved in 200 mL of N-methylpyrrolidone, and then the conductive agent and the positive electrode material were added and mixed, and then placed in a homogenizer for stirring, first homogenized at 800 rpm for 30 s, and then homogenized at 2000 rpm for 15 min to obtain a positive electrode slurry; A2. Place aluminum foil on the surface of the coating machine, pour in the positive electrode slurry prepared in step A1, adjust the scale of the knife to 12μm, remove it when it is coated at a uniform speed to the end, and then place it in an oven at 120°C to dry for 1h, then roll it, and then punch it manually to obtain the positive electrode for solid-state batteries.

[0025] Embodiment 6

[0026] A1. After drying 90 g of the positive electrode material obtained in Example 4, 9 g of polytetrafluoroethylene and 15 g of the conductive agent obtained in Example 2 in an oven for 12 h, polytetrafluoroethylene was first dissolved in 200 mL of N-methylpyrrolidone, and then the conductive agent and the positive electrode material were added and mixed, and then placed in a homogenizer for stirring, first homogenized at 800 rpm for 30 s, and then homogenized at 2000 rpm for 15 min to obtain a positive electrode slurry; A2. Place aluminum foil on the surface of the coating machine, pour in the positive electrode slurry prepared in step A1, adjust the scale of the knife to 12μm, remove it when it is coated at a uniform speed to the end, and then place it in an oven at 120°C to dry for 1h, then roll it, and then punch it manually to obtain the positive electrode for solid-state batteries.

[0027] Embodiment 7

[0028] A1. After drying 100 g of the positive electrode material prepared in Example 3, 12 g of polytetrafluoroethylene and 20 g of the conductive agent prepared in Example 2 in an oven for 12 h, polytetrafluoroethylene was first dissolved in 200 mL of N-methylpyrrolidone, and then the conductive agent and the positive electrode material were added and mixed, and then placed in a homogenizer for stirring, first homogenized at 800 rpm for 30 s, and then homogenized at 2000 rpm for 15 min to obtain a positive electrode slurry; A2. Place aluminum foil on the surface of the coating machine, pour in the positive electrode slurry prepared in step A1, adjust the scale of the knife to 12μm, remove it when it is coated at a uniform speed to the end, and then place it in an oven at 120°C to dry for 1h, then roll it, and then punch it manually to obtain the positive electrode for solid-state batteries.

[0029] Comparative Example 1 The conductive agent in Example 7 was replaced by conductive carbon black of equal mass, and the remaining steps were the same as those in Example 7 to prepare a positive electrode.

[0030] Comparative Example 2 A commercially available positive electrode for solid-state batteries was used.

[0031] The positive electrodes obtained in Examples 5, 6, 7 and Comparative Examples 1 and 2 were assembled into button-type batteries and performance tests were performed. The results are shown in the following table:

[0032] It can be seen from the above table that the positive electrode prepared in the embodiment of the present invention has a higher capacity, rate performance, electrical performance and cycle performance as a battery than the comparative example, and it can be seen from Examples 5, 6, 7 and Comparative Example 1 that with the continuous increase in the content of the conductive agent, the various performances of the battery are improved. Therefore, the present invention has important application value in the field of lithium ion battery technology.

[0033] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0034] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.

Claims

1. A method for preparing a positive electrode for a solid-state battery, characterized in that: The following steps are involved: A1. Place the positive electrode material, binder and conductive agent in an oven, first dissolve the binder in N-methylpyrrolidone, then add the conductive agent and positive electrode material, mix and place in a homogenizer to stir to obtain positive electrode slurry; A2. Place aluminum foil on the surface of the coating machine, pour in the positive electrode slurry prepared in step A1, adjust the scale of the knife to 12μm, remove it when it is coated at a uniform speed to the end, and then place it in an oven at 120°C to dry for 1h, then roll it, and then punch it manually to obtain the positive electrode for solid-state batteries.

2. The method for preparing a positive electrode for a solid-state battery according to claim 1, characterized in that: The conductive agent is prepared by the following steps: S1. Mix multi-walled carbon nanotubes with concentrated sulfuric acid and concentrated nitric acid, and perform ultrasonic treatment. The ultrasonic time is 4 hours and the ultrasonic temperature is 60°C. After the ultrasonic treatment, reflux at 100°C for 5 hours. After the reaction is completed, cool, filter, wash the filtrate with distilled water until it is neutral, dry, and grind to obtain pre-modified carbon nanotubes; S2, vinyl triethoxysilane, AIBN and N, N-dimethylformamide were mixed and stirred evenly, 2-mercaptopyridine was slowly added, and the mixture was reacted at 70° C. for 4 h. After the reaction was completed, the mixture was rotary evaporated, purified by column chromatography, and rotary evaporated to obtain an intermediate; S3, mixing the pre-modified carbon nanotubes with the ethanol aqueous solution, adding them to a magnetic stirring device, starting stirring, dispersing for 30 minutes, evacuating the device, introducing N2 gas, adding the intermediate, starting heating, setting the temperature to 80°C, turning on condensation water, reacting for 4 hours, and completing the reaction, filtering, washing, and drying to obtain; S4. Add the modified carbon nanotubes and carbon black into a ball mill, and mix them evenly by ball milling to obtain a conductive agent.

3. The method for preparing a positive electrode for a solid-state battery according to claim 2, characterized in that: In step S1, the ratio of the amount of multi-walled carbon nanotubes, concentrated sulfuric acid, and concentrated nitric acid is 1 g: 60 mL: 40 mL.

4. The method for preparing a positive electrode for a solid-state battery according to claim 2, characterized in that: In step S2, the ratio of the amount of vinyltriethoxysilane, AIBN, N,N-dimethylformamide, and 2-mercaptopyridine is 18.8 g:0.3 g:100 mL:11.1 g.

5. The method for preparing a positive electrode for a solid-state battery according to claim 2, characterized in that: In step S3, the ratio of the amount of the pre-modified carbon nanotubes, the ethanol aqueous solution, and the intermediate is 1.0 g: 100 mL: 8.5 g.

6. The method for preparing a positive electrode for a solid-state battery according to claim 2, characterized in that: In step S4, the ratio of modified carbon nanotubes to carbon black is 5g:2g.

7. The method for preparing a positive electrode for a solid-state battery according to claim 1, characterized in that: The positive electrode material is prepared by the following steps: The lithium-rich manganese-based ternary material and PVP-K30 were dissolved and dispersed in a mixed solution of anhydrous ethanol and distilled water, and then ammonium dihydrogen sulfate was added. After ultrasonic treatment for 15 minutes, the components were evenly dispersed. Then, after continuous stirring for 3 hours, they were dried in a vacuum drying oven at 100°C for 6 hours, and finally calcined at 450°C for 5 hours and naturally cooled to room temperature to obtain the positive electrode material.

8. The method for preparing a positive electrode for a solid-state battery according to claim 7, characterized in that: The usage ratio of the lithium-rich manganese-based ternary material, PVP-K30 and ammonium dihydrogen sulfate is 10g:6.5g:8.4g.

9. The method for preparing a positive electrode for a solid-state battery according to claim 1, characterized in that: The raw materials are calculated in parts by weight as follows: 80-100 parts of positive electrode material, 6-12 parts of binder, and 10-20 parts of conductive agent.

Citation Information

Patent Citations

  • Preparing method of highly conductive lithium iron anode material of lithium ionic cell

    CN101425576A

  • Preparation method of hydroxylated multi-wall carbon nanotube-polysilane composite material

    CN103113593A

  • Method for improving performance of spinel lithium-rich lithium manganate positive electrode material by use of acid salt

    CN105977471A

  • Positive electrode active material, preparation method thereof and lithium battery

    CN112151773A

  • Negative electrode material, composite negative electrode material and preparation method thereof, secondary battery and terminal equipment

    CN115000403A